Optimizing Marketing Strategies for Micro, Small, and Medium Enterprises (MSMEs) through Digital Marketing Training - Afandi, Muhammad Misbahul; Astiwi, Wuri; Putri, Helena Anggraeni; Wahyuni, Nur; Alghiffari, Eka Kevin; Siswanto, Deny Hadi (Indonesian Scientific Publication, 2024)
The objective of this training activity is to enhance the skills and understanding of the community regarding digital marketing. The training consists of three phases: pre-activity, implementation, and monitoring and evaluation. It includes relevant materials, practical exercises, and evaluation tests, and was attended by 30 participants from the general public and MSME practitioners in Sleman Regency, held on July 26-27, 2024. The results show that 97% of participants passed the test, while 3% did not pass due to absence during the exam. The highest score achieved in the digital marketing training was 97.5 (by one participant), the lowest was 70 (by two participants), and the average evaluation score for each participant was 80.94. Overall, the training was successfully conducted and met the expected objectives.